Experimental Study of Vibration of Shaft-Rotor System Due to Imbalance - Asmara Yanto; Rozi Saferi (LP2M - Institut Teknologi Padang, 2017)
In this study, vibration of shaft-rotor system as a part of rotating machinery prototype due to imbalance has been monitored, processed and analyzed by a dynamic signal analyzer virtual instrument (DSA VI). The rotating machinery prototype consists of an AC induction motor, a pulley-belt system, and a shaft-rotor system supported by two bearings. Two discs were placed between two bearing housings. On both discs are added and placed additional mass as unbalance mass on shaft-rotor system. Unbalance mass placement is varied with different of angle orientations i.e. 0o, 30o, 60o, 90o, 120o, 150o and 180o between on both discs. DSA VI consists of four micro-electro-mechanical system (MEMS)-based accelerometers type ADXL335 that placed on the bearing housings, a data acquisition device and a data analyzer device. The four accelerometers serve to convert the mechanical quantities of measured vibration acceleration into electrical quantities in mV. Vibration signal in mV is acquired by the data acquisition device. Data sampling rate is set at control panel of the data analyzer device. Measurable vibrations in the time domain are displayed by the data analyzer device in a computer. Vibration in time domain is transformed into frequency domain by using fast fourier transfrom (FFT) method. From this experimental study of vibration of shaft-rotor system due to imbalance obtained the highest vibration amplitude for unbalance mass placement with different of angle orientation is 30o between on both discs. If unbalance mass placement with different of angle orientation is greater than 30° between on both discs, then amplitude of vibration due to imbalance will decreases.